Polar vasculosis is associated with better kidney outcome in type 2 diabetes with biopsy‐proven diabetic kidney disease: A multicenter cohort study - Miho Shimizu; Kengo Furuichi; Tadashi Toyama; Masayuki Yamanouchi; Junichi Hoshino; Shinji Kitajima; Akinori Hara; Yasunori Iwata; Norihiko Sakai; Yukio Yuzawa; Hiroshi Kitamura; Hiroshi Sato; et al. (Journal of Diabetes Investigation, 2023)
ABSTRACT Aims/Introduction This multicenter cohort study retrospectively assessed the association between polar vasculosis and the progression of diabetic kidney disease (DKD) in type 2 diabetes. Materials and Methods We enrolled 811 patients with type 2 diabetes, biopsy‐proven DKD, and proteinuria (≥0.15 g/g creatinine [g/day]). The association between polar vasculosis and other kidney lesions was explored. The outcome was DKD progression defined as a composite of renal replacement therapy initiation or 50% decline in estimated glomerular filtration rate (eGFR) from baseline. Results Of the 811 cases, 677 (83.5%) had polar vasculosis. In multivariate logistic regression analysis, subendothelial widening of the glomerular basement membrane, glomerulomegaly, glomerular class in the Renal Pathology Society classification ≥IIb, vascular lesions, age, eGFR, and hemoglobin A1c were positively associated with polar vasculosis, whereas interstitial fibrosis and tubular atrophy (IFTA) was negatively associated with polar vasculosis. During a median follow‐up of 5.2 years, progression of DKD occurred in 322 of 677 (7.4 events/100 person‐years) and 79 of 134 (11.4 events/100 person‐years) cases with and without polar vasculosis, respectively. Kaplan–Meier analysis showed that polar vasculosis was associated with lower cumulative incidences of DKD progression. Multivariate Cox regression analyses showed that polar vasculosis was associated with a lower risk of DKD progression, regardless of eGFR or proteinuria subgroups. These associations between polar vasculosis and better kidney outcome were unchanged considering all‐cause mortality before DKD progression as a competing event. Conclusions This study showed that polar vasculosis of DKD was associated with less advanced IFTA and a better kidney outcome in type 2 diabetes with proteinuria.